Pose-Based Suspicious Activity Detection Using YOLOv12n and MediaPipe in Smart Surveillance Systems - Bowo Nugroho; Bima Prihasto; Aninditya Anggari Nuryono; Ahmad Rusdianto Andarina Syakbani; Nawfal Alhadi; Rionando Soeksin Putra; Ilham Al Basith (Department of Electrical Engineering and Informatics, Vocational College, Universitas Gadjah Mada, 2026)
Detecting suspicious activity in video surveillance is critical for public safety. Early identification of pre-incident behaviors, such as